Considerations on the Present and Future of Buffalo in Terms of Sustainability - Stelian Sertu; Maria Paraschivescu; Maria Voiculescu; Marinela Enculescu (Scientific Papers Animal Science and Biotechnologies, 2023)
This paper is a brief analysis on the evolution of the buffalo herds nationally and internationally. It is noted that depending on the size of herds in each country may speak of countries with active population, the countries of Italy in increasing Asian buffaloes for milk production or animal labor and Brazil as countries with vulnerable populations, the number of animals decreasing, as situation in Romania. Among the key factors that have decreased the buffalo herd of buffaloes are low fertility and low energy conversion of feed energy product compared to steers. In contrast to Romania is situated countries as Brazil and Italy recorded a large increase efectvelor buffalo .. If primary production in Brazil is produced in Italy tractive force main target is the production of milk, which is offering very little in Europe. For future incrase buffalo in Romania is of great importance good milk price and the possibility of using coarse fodder. Growth strategy in Romania is transforming buffalo population of vulnerable indigenous active focusing on increasing its fertility.